Peran Pelatihan dan Pengembangan Dalam Menciptakan Perilaku Kerja Yang Inovatif dan Efektifitas Organisasi - Siti Rosmayati; Engkus Kuswarno; Achmad Mudrikah; Yosal Iriantara (Coopetition : Jurnal Ilmiah Manajemen, 2021)
This research uses descriptive qualitative research by creating a simple model in the development of training to create innovative and effective work in the workplace. Innovation is the development of work according to the skills of its employees. If the thoughts and actions of employees are creative and innovative, then innovation emerges. The need for innovation arises when a person tries to do cognitive work that is not routine. Learning and development is very important among various development resource practices that help employees to continuously update the knowledge, skills and attitudes required for innovation. It is important for the Organization to focus on eliciting innovative behavior among its employees to enable innovation. Non-routine work helps employees to be innovative and understand the importance of being innovative and learn the skills that are prerequisites for innovative behavior. This conceptual model tries to explore how non-routine work is carried out effectively through innovative work behaviors.